2018
DOI: 10.1590/s0004-2803.201800000-87
|View full text |Cite
|
Sign up to set email alerts
|

Potential Preventive Effect of Lactobacillus Acidophilus and Lactobacillus Plantarum in Patients With Polyps or Colorectal Câncer

Abstract: BACKGROUND: Colorectal cancer is one of the major causes of death worldwide. Many studies have been done on the biology of its formation as well as its treatment in recent years. One of the factors involved in the formation or treatment of this malignancy can be attributed to the microbial flora in the intestine. OBJECTIVE: This study investigate the potential preventive effect of Lactobacillus acidophilus and Lactobacillus plantarum in patients with polyps or colorectal cancer (CRC). METHODS: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…The study used 16 S rRNA to conduct preliminary gene detection on 77 samples of CRC, polyps, and healthy subjects, and used absolute realtime PCR to determine the copy number of bacteria per Gram of feces. The results confirmed that taking L. acidophilus and L. plantarum in people with a family history of CRC and patients with polyps may be a method to prevent, treat, or alleviate CRC (Zinatizadeh et al, 2018). In addition, Lactobacillus casei BL23, a probiotic-specific strain, can inhibit colitis-associated CRC, which can be used as a potential new strategy for the prevention and treatment of CRC.…”
Section: Probiotics Prebiotics Synbiotics and Postbioticssupporting
confidence: 61%
“…The study used 16 S rRNA to conduct preliminary gene detection on 77 samples of CRC, polyps, and healthy subjects, and used absolute realtime PCR to determine the copy number of bacteria per Gram of feces. The results confirmed that taking L. acidophilus and L. plantarum in people with a family history of CRC and patients with polyps may be a method to prevent, treat, or alleviate CRC (Zinatizadeh et al, 2018). In addition, Lactobacillus casei BL23, a probiotic-specific strain, can inhibit colitis-associated CRC, which can be used as a potential new strategy for the prevention and treatment of CRC.…”
Section: Probiotics Prebiotics Synbiotics and Postbioticssupporting
confidence: 61%
“…Since cancer is a multifactorial disease, any generalization of effective factors in the induction of cancer should be done with caution. In a study recently conducted by our research team to determine the role of Lactobacillus in inducing or preventing the spread of adenoma or colorectal cancer (26) , lactobacilli may could have a preventive role in the induction or spread of malignancy. The results of this study and our previous study (26) , indicate the dual role of bacteria in preventing or inducing malignancy.…”
Section: Real-time Quantification Pcr Of Total Enterococcus Faecalis mentioning
confidence: 99%
“…In a study recently conducted by our research team to determine the role of Lactobacillus in inducing or preventing the spread of adenoma or colorectal cancer (26) , lactobacilli may could have a preventive role in the induction or spread of malignancy. The results of this study and our previous study (26) , indicate the dual role of bacteria in preventing or inducing malignancy. These results could be an introduction to more extensive studies on the microbiome of colorectal cancer patients compared to healthy people to provide more clarity and broader scope to determine the role of bacteria in the health and illness of individuals.…”
Section: Real-time Quantification Pcr Of Total Enterococcus Faecalis mentioning
confidence: 99%
“…As members of the gut microbiota, lactic acid bacteria (LAB), especially Lactobacillus, exert health bene ts for the host when administered in adequate amounts [13]. Several lines of evidence demonstrated that the supplementation of LAS could act as a prophylactic strategy for the prevention and cure of colorectal cancer as a result of their probiotic properties [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%